The function of BoTCP25 in the regulation of leaf development of Chinese kale - Zeng, Jiajing; Yang, Mengyu; Deng, Jing; Zheng, Dongyang; Lai, Zhongxiong; Wang-Pruski, Gefu; XuHan, Xu; Guo, Rongfang (Frontiers in Plant Science, 2023)
As a functional organ for photosynthesis, the leaves are vital to the growth and development of plants and affect the yield and flavor quality of leafy vegetables. Chinese kale is a vegetable that uses the tender bolting stem and young leaves as the edible part. However, the transcriptional mechanisms regulating leaf development and morphogenesis during the growth of Chinese kale are still poorly understood. We have identified the high expression of BoTCP25 in Chinese kale leaves in the previous study. To understand the function of BoTCP25 in the leaves, we have conducted GUS staining of BoTCP25 promoter-transformed Arabidopsis plants showing that BoTCP25 was widely expressed throughout the growth period. We have also obtained overexpressed BoTCP25 transgenic Arabidopsis thaliana and Chinese kale plants. Phenotypic analysis showed that heterologous overexpression of TCP25 promoted an increase in leaf number and leaf area in Arabidopsis. In contrast, overexpression of TCP25 in kale affected the location and number of metamorphic leaf-bearing. Analysis of gene expression in Chinese kale overexpression plants showed that BoNGA3 has a similar expression pattern to BoTCP25 and is likely to be involved in regulating leaf development by BoTCP25. Yeast one-hybrid experiments verified that BoTCP25 can bind to the promoter of BoNGA3. The results suggest that a BoTCP25-BoNGA3 module may be involved in Chinese kale leaf development. In addition, BoTCP25 expression responds to hormonal conditions. In conclusion, our study suggests that the BoTCP25-BoNGA3 module plays a vital role in plant leaf development and morphogenesis.